Factors Associated Nurses Reporting of Patient Safety Incidents in Inpatient Wards : A Cross-Sectional Study - Sri Rahayu; Idyatul Hasanah; Zulkahfi Zulkahfi (An Idea Nursing Journal, 2026)
Background: Reporting of Patient Safety Incidents (PSIs) is a critical element of patient safety programs, supporting quality improvement and the prevention of recurrent adverse events. Objective: This study investigated factors associated with nurses’ compliance with PSI reporting in a hospital environment Methods: A quantitative cross-sectional design was employed from 5 to 30 January 2026 in the inpatient wards of Siti Hajar Islamic Hospital, Mataram. Sixty-nine nurses participated through total sampling. Independent variables included perceived knowledge, non-punitive culture, leadership support, and accessibility of the reporting system; the dependent variable was compliance with PSI reporting. Data collection utilized a structured Likert-scale questionnaire, and analysis was conducted using the Spearman Rank correlation test and exploratory multivariate logistic regression. Result: Compliance with PSI reporting was generally low. Most participants exhibited insufficient perceived knowledge, identified the non-punitive culture as inadequate, and reported restricted accessibility to the reporting system. Both bivariate and multivariate analyses revealed no statistically significant associations between the independent variables and PSI reporting compliance (all p > 0.05). In multivariate analysis, non- punitive culture (OR = 2.046, p = 0.155) and leadership support (OR = 1.315, p = 0.587) showed positive but non-significant associations with reporting compliance. Conclusion: Nevertheless, the findings indicate that organizational culture and leadership may be important targets for enhancing patient safety practices. Further research with larger sample sizes is recommended to validate these results.